Bioconversão de resíduos agroindustriais por micro-organismos do bioma amazônico produtores de enzimas lignocelulolíticas - Scheufele, Fabiano Bisinella (2012)
Lignocellulosic biomass has high yields of cellulose which can be hydrolyzed to fermentable carbohydrates. Global generation of agro-industrial wastes grows simultaneously with the sector development resulting at the accumulation of lignocellulosic residues leading environmental pollution and loss of potential materials for the bioconversion to a wide range of high added value products, such as biofuels. Recently, the search of renewable sources of energy has grown, due to the depleting of fossil fuels, increasing the possibility at the conversion of the lignocellulosic biomass via hydrolytic enzymes. The aim of this work was evaluate cellulases production by lignocellulolytic fungi from the Amazonic biome aiming at the bioconversion of the agro-industrial residues. Submerged and solid-state fermentations were performed to select the microorganism with superior cellulase productive capacity. The influence of parameters such as pH, surfactant induction (Tween 80), aeration and agitation, besides the alkaline oxidative treatment of the sugarcane bagasse. Statistical design were carried out to estimate the influence of the moisture and the initial pH at cellulases production by solid-state fermentation. Trichoderma sp. and Aspergillus niger performed the best production of enzymes, where the highest yields of total cellulase were obtained by agitated submerged fermentation with sugarcane bagasse pretreated with H2O2 (1%) reaching 0.265 U.mL-1 (12.915 U.g-1) by Trichoderma sp. at the sugarcane bagasse, and 0.155 U.mL-1 (7.549 U.g-1) by Aspergillus niger. Through solid state fermentations with the pretreated sugarcane bagasse the influence of initial pH and the moisture were evaluated by statistical design. In the case of the Trichoderma sp. both parameters were significant at the cellulase production, as well as the synergistic interaction, within the confidence interval of 95%, yielding 0.167 U.mL-1 (2.695 U.g-1), at the pH 7.0 and 1:9 solid-liquid ratio. For Aspergillus niger only pH was significant and the cellulase content obtained was 0.098 U.mL-1 (1.695 U.g-1) at pH 7.0. Finally, a cellulase produced by Trichoderma sp. at solid state fermentation and a commercial enzyme were used at enzymatic hydrolysis tests. The parameters hydrolysis time, enzyme dilution, concentration of Tween 80 and solid-liquid ratio of sugarcane bagasse were evaluated. The significant variables were then optimized by a central composite rotational design. The strain of Trichoderma sp. from the Amazon biome showed potential at the cellulase production and the treated sugarcane bagasse was a fine substrate for the enzymatic production.